The role of coaches' passion and athletes' motivation in the prediction of change-oriented feedback quality and quantity - Carpentier, J.; Mageau, G. A. (Psychology of Sport and Exercise, 2014)
Objectives: The provision of an autonomy-supportive change-oriented feedback has been identified as a crucial coaching behaviour that is beneficial for athletes' phenomenological experience and performance. Based on past research that focused on the determinants of other autonomy-supportive coaching behaviours, the present study investigates coaches' passion toward coaching and coaches' perceptions of their athletes' motivation as potential determinants of the quality (i.e., the extent to which it is autonomy-supportive) and quantity of the change-oriented feedback that coaches provide. Design: Quantitative cross-sectional study using a dyadic approach. Methods: In total, 280 athletes and 48 coaches participated in this study. Coaches and athletes both filled out a questionnaire after a training session. Coaches reported their passion and evaluated their athletes' motivation, whereas the provision of feedback was assessed by athletes. HLM analyses were used to take into consideration the hierarchical structure of the data. Results: HLM analyses showed that only obsessive passion was a significant predictor of change-oriented feedback quality. The more coaches reported having an obsessive passion toward coaching, the less their change-oriented feedback was autonomy supportive. Results pertaining to feedback quantity showed that the more coaches were obsessively passionate and the more they perceived their athletes as being motivated, the more they gave change-oriented feedback. In contrast, when controlling for athletes' age and gender, the more coaches were harmoniously passionate, the less change-oriented feedback they tended to give. Conclusions: Results are discussed in light of their contribution to the passion, self-fulfilling prophecies and feedback literature.